Validity and Reliability of Mathematical Reasoning Ability Instruments in High Schools with Winsteps - Syahwa, Keysha Alifia; Gustia, Satria Kamal; Faradillah, Ayu; Ulfah, Syafika (Pattimura Proceeding, 2024)
The mathematical reasoning ability in understanding mathematical material in high school students still has not touched perfect scores. A valid and reliable instrument is needed in measuring mathematical reasoning skills in students. Validity and reliability testing of the instrument is carried out to ensure whether an instrument can be used to provide accurate results in a measurement being performed. Therefore, this study aims to determine the level of validity and reliability of mathematical reasoning skills in students using Winsteps. The method used in this study is a quantitative survey method, with 252 respondents in high schools in Jakarta. This study uses 3 indicators that are a reference in measuring the mathematical reasoning ability possessed by students. The validity test on the instrument shows that all items on the instrument are valid because they meet the criteria of MNSQ, ZSTD, and Pt Mean Corr except for item 1 which has a ZSTD value of > 2.0 and item 3 has a ZSTD value of < -2.0. Meanwhile, the reliability test obtained an Alpha Cronbach calculation of 0.74 which means that the value of the reliability item is high so that the instrument is declared reliable for use. The DIF analysis using winsteps shows that all question items used in the instrument are valid because none of the question items contain bias referring to the DIF Analysis criteria, namely the DIF Contrast value > 0.5 and the probability value < 0.05 where all the value of the question items actually obtained a DIF Contrast value of < 0.5 and a probability value > 0.05.